Bulletin 64 The Titaniferous Iron Ores - Joseph T. Singewald (The National Institute for Occupational Safety and Health (NIOSH), 1913)
The term "titaniferous magnetite" is used to designate those mag- netic ores of iron that carry more than 2 or 3 per cent of titanium. Large and easily workable deposits of these ores occur in different parts of the world, and have attracted attention for many years. Under present furnace practice, however, the smelting of these ores is both difficult and expensive, and for that reason they are not accepted by furnaces, so that the deposits are practically worthless. The problem of finding a feasible method of utilizing these ores has naturally been attractive, and numerous attempts have been made to solve it. Experiments to that end embrace two lines of investigation. The one that has been the more frequently tried is the elimination of the titanium from the ores, so as to make possible their smelting in the usual way. The other is the devising of a method of smelting by which titaniferous ores may be reduced as economically as are non- titaniferous ores. The former method involves a physical process, the latter a chemical process. The measure of success attainable by the first method depends entirely on the relations between the iron and the titanium in the ore. Views in regard to these relations have been divergent. Some investi- gators have believed the titanium to occur as a part of the magnetite molecule, in which case, of course, any process of mechanical separa- tion would be impossible. Others have believed that the titanium occurs as the mineral ilmenite, and that the ores are aggregates of magnetite and ilmenite. In this case a separation of the two minerals is theoretically possible. Magnetite is highly magnetic; ilmenite is nonmagnetic or only feebly magnetic. Crushing and magnetic con- centration should separate them. Numerous experiments in mag- netic separation have been made with various degrees of success, but rarely has more than a very imperfect separation been obtainable. In other words, some of the titanium exists in a separable form and some in an inseparable form, and the ratio between the two forms is